Victim Precipitation: An Outdated Construct or an Important Forensic Consideration?. Issue 3 (27th May 2021) - Petherick, Wayne; Kannan, Arathi; Brooks, Nathan
ABSTRACT: Risk assessment and threat management are important components of crime control and crime prevention, with the results of assessments having a significant impact on personal and community safety. There may also be important legal implications arising from these if individuals are deemed to be a risk to others. There is evidence showing that traditional risk assessment tools do not consider the victim's role, even though it is important to incorporate into assessment and management to gain a full understanding of the risk and the intervention to decrease or eliminate risk or harm. This paper reviews the construct of victim precipitation, where the victim may actively do something or has characteristics that entice or incite an offender. Victim precipitation is a controversial topic that has not been the subject of much recent research, and its relationship to risk assessment and threat management has therefore been largely ignored. This paper argues that excluding victim precipitation has a negative impact on the conclusions derived from risk assessment and threat management. This is done by analyzing victim precipitation, risk assessment, and threat management in detail which helps understand the role precipitation plays.